(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sibero MT, Frederick EH, Sabdono A, Wijayanti DP, Pringgenies D, Radjasa OK, Zilda DS, Murwani R. 2022. First report of seaweed-associated yeast from Indonesia: Species composition and screening of their polysaccharides-degrading enzymes. Biodiversitas 23: 1408-1419. Yeast has been widely utilized in various industries due to its enzyme properties. Therefore, plenty of studies focus on exploring yeast biodiversity from diverse sources. However, there are limited reports regarding marine yeast biodiversity and its potential from Indonesia. This study aimed to isolate and identify the seaweed-associated yeast from Jepara in Central Java and Sepanjang Beach in Gunung Kidul, Yogyakarta, then examined their potential to produce extracellular polysaccharides-degrading enzymes (EPEs). Marine yeasts were isolated using standard marine agar (STD) and potato dextrose agar (PDA). All isolates were characterized by their salinity tolerance, morphology, and species confirmation using DNA barcoding. Three EPEs consisting of agarase, alginate-lyase, and carrageenase were screened using polysaccharides-enriched agar media. A specific agarase encoding gene was detected with specific primers. In total, 21 seaweed-associated yeast were successfully isolated from 6 seaweeds and noted as facultative marine yeast. The DNA barcoding study discovered that these yeasts belonged to 5 genera, consisted of Aureobasidium, Candida, Debaryomyces, Hortaea, and Rhodotorula. Moreover, Candida was noted as the most abundant genus (71.42%). It was noted that Hortaea werneckii MTJ.11 and MTJ.13 were positive for all enzymes; Aureobasidium melanogenum MTGK.31 gave a positive result for agarase and carrageenase; while [Candida] zeylanoides MTGK.23 only exhibited alginate-lyase activity. Unfortunately, none of the primers used to detect the presence of genes encoding polysaccharide-degrading enzymes were successfully amplified.